Soluble SARS-CoV-2 Spike glycoprotein: considering some potential pathogenic effects - Azzarone, Bruno; Landolina, Nadine; Mariotti, Francesca Romana; Moretta, Lorenzo; Maggi, Enrico (Frontiers in Immunology, 2025)
The soluble S1 subunit of Spike protein (SP) from the SARS‐CoV-2 of different variants of concern (VOCs) may directly bind and activate human NK cells in vitro through the engagement of the toll-like receptor (TLR) 2 and TLR4. This mechanism revealed a novel pathogenic role played by NK cells not only in the different phases of disease but also in the post-acute sequelae of COVID-19 (PASC) and some post-vaccination side effects. In addition to its binding to angiotensin-converting enzyme 2 (ACE2), which mediates virus attachment and cell entry, soluble SP triggers several active receptors/molecules expressed by many cells, inducing, in turn, type I/III interferon decrease, altered autophagy and apoptosis, the release of inflammatory cytokines and chemokines, complement activation and endothelial damage, which favour clotting events. In this review, we discuss the hypothesis that circulating SP, exerting multiple biological activities, can explain the heterogeneity of the clinical outcomes of severe COVID-19, PASC and post-vaccine-related effects. Recent reports have clearly indicated that soluble SARS-CoV-2 and post-vaccination SP trigger the same cascade of events, acting on the immune response and promoting defined adverse events. Factors hindering the pathological activity of soluble SP are the SP plasma levels, the age of the infected/vaccinated people and the efficiency of protein synthesis of ectopic targets triggered by soluble SP, as well as the specificity, the titre and the affinity of anti-SP antibodies elicited by the infection. At present, the risk/benefit ratio is largely in favour of vaccination; however, the excessive and persistent ectopic production of synthetic SP should be systematically analysed. This would allow for the identification of subjects at risk for major adverse events and to answer the urgent need for efficient vaccines that provide long-lasting activity with minimal side effects.